Endopedon yang Berkembang dari Batuan Ultrabasa di Desa Bentok Darat Kabupaten Tanah Laut, Kalimantan Selatan - Ahmad Fahrezal; Syaifuddin Syaifuddin; Meldia Septiana (Acta Solum, 2024)
Although ultramafic rocks are widespread in Indonesia and have the potential to influence soil properties, studies on the genesis and properties of soils formed from these rocks, especially to understand the characteristics of the lower defining horizon or endopedon, are still limited. This study aims to identify the endopedons formed, which developed from the ultrabasic rocks. This research is descriptive, soil profile points are determined by purposive sampling method by considering that points are true ultrabasic rock distribution. Observations made in this study include observations in the field and observations in the laboratory. The data from the description and laboratory analysis were used as reference for identifying endopedon. Endopedon determination refers to the Keys to Soil Taxonomy 2014 , the twelfth edition. The oxic horizon in Profile-1 is found at a depth of 7 cm to 37 cm from the soil surface with the horizon codes Bo. The Oxic horizon in Profile-2 is located at a depth of 20 cm to 106 cm from the soil surface with the horizon codes Bo1, Bo2. Latosolization is the process that causes the formation of the oxic horizon. The study site is also an area with a wet tropical climate that supports the formation of the oxic horizon.